The Influence Of Organizational Climate And Leadership On The Performance Of Sekolah Menengah Atas Cinta Budaya Teachers - Edward A. Lbn. Raja*; Rozaini Rozaini; Rita Kartika Dongoran; Adiwima Zebua; Endang D. Sinaga (Universitas Syiah Kuala, 2024)
Knowledge is the basic need of every individual. Because of the importance of education, the government requires education for at least 9 years and it is recommended that more than that The formulation of the problem in this study is as follows: